A comparison of pain on intravenous injection to two formulations of Propofol, one containing medium chain and long chain triglycerides and the other without medium chain and long chain triglycerides - Pandey, Swati; Kiran, S. S. Smruthi (International Journal of Research in Medical Sciences, 2019)
Background: To assess and compare the Visual Analog Scale (VAS) for pain on intravenous injection in patients receiving the two different formulations of Propofol. Methods: Total 170 eligible patients were randomized into Group A receiving Propofol MCT/LCT and Group B receiving Propofol LCT. After standard pre-anaesthetic preparation and baseline values recording, the blinded investigator recorded pain intensity after injection of 1mL study drug propofol, using Visual Analog Scale (0-10). Haemodynamic parameters were recorded every minute for 5 minutes. Calculated Propofol dose was injected in 20 seconds, and signs of pain (hand withdrawal, grimacing) were noted. After patient regained full consciousness, recall of injection pain was asked for. Results: The proportion of patients who experienced pain was similar in both groups (group A: 76/85 =89.41%, group B: 81/85 = 95.29%; statistically not significant (p value=0.247). Patients in group A had longer time for pain onset (11.3 seconds-group A Vs 9.8 seconds-group B; statistically significant, p value =0.008). Pain on injection was higher in Propofol LCT group as compared to Propofol MCT/LCT (VAS scores of group A=3.94±2.0 vs group B = 5.49±1.96; statistically significant; p value = 0.0018). Full dose of Propofol MCT/LCT produced significantly less pain when compared to Propofol LCT (p value = 0.0424). Recall of pain was comparable between the groups. Haemodynamic parameters (Heart rate and Mean Arterial Pressure) remained comparable in both groups. Conclusions: Pain on injection was higher and statistically significant in Propofol LCT group as compared to Propofol MCT/LCT.